2021
DOI: 10.1371/journal.pone.0256807
|View full text |Cite
|
Sign up to set email alerts
|

The antagonistic mechanism of Bacillus velezensis ZW10 against rice blast disease: Evaluation of ZW10 as a potential biopesticide

Abstract: Rice blast, caused by the fungus Magnaporthe oryzae, is one of the three major diseases affecting rice production and quality; it reduces rice grain yield by nearly 30%. In the early stage of this study, a strain of Bacillus velezensis with strong inhibition of M. oryzae was isolated and named ZW10. In vitro assays indicated prolonged germination time of conidia of M. oryzae treated with the antifungal substances of ZW10, 78% of the conidia could not form appressorium, and the conidial tubes expanded to form v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…Although the antagonistic efficacies between the different biocontrol agents were not compliant to be quantitively compared when the individual tests were not conducted on the same conditions, from the comparative literature analysis, we might still evaluate B. velezensis BR-01 to have the potential being a strong and broad-spectrum biocontrol agent in rice disease control. Currently, there have been numerous reports about the antagonistic effects and biocontrol efficacies of B. velezensis strains on M. oryzae, some of which were registered as the bacterial pesticides used in rice production (Chen et al, 2021). From our dual culture tests, B. velezensis BR-01 has an 83.7% relative inhibition rate on M. oryzae, which is comparable to most of other B. velezensis strains on M. oryzae (Sha et al, 2020;Chakraborty et al, 2021).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Although the antagonistic efficacies between the different biocontrol agents were not compliant to be quantitively compared when the individual tests were not conducted on the same conditions, from the comparative literature analysis, we might still evaluate B. velezensis BR-01 to have the potential being a strong and broad-spectrum biocontrol agent in rice disease control. Currently, there have been numerous reports about the antagonistic effects and biocontrol efficacies of B. velezensis strains on M. oryzae, some of which were registered as the bacterial pesticides used in rice production (Chen et al, 2021). From our dual culture tests, B. velezensis BR-01 has an 83.7% relative inhibition rate on M. oryzae, which is comparable to most of other B. velezensis strains on M. oryzae (Sha et al, 2020;Chakraborty et al, 2021).…”
Section: Discussionsupporting
confidence: 57%
“…Currently, there have been numerous reports about the antagonistic effects and biocontrol efficacies of B. velezensis strains on M . oryzae , some of which were registered as the bacterial pesticides used in rice production ( Chen et al, 2021 ). From our dual culture tests, B. velezensis BR-01 has an 83.7% relative inhibition rate on M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a semi-commercial large-scale study, the efficacy of these strains was found to be comparable to that of two commercial BCAs, but slightly lower than that of a commercial synthetic fungicides [ 47 , 59 ]. The considerable biological control activity of a Bacillus velezensis strain named ZW10, as well as its ability to boost host defenses, make it a potential biopesticide for rice blast biocontrol caused by the fungus Magnaporthe oryzae [ 60 ]. The commercially available B. amyloliquefaciens FZB42 product has considerably decreased lettuce bottom rot caused by R. solani .…”
Section: Rhizosphere As a Potential Reservoir Of Biopesticidesmentioning
confidence: 99%
“…Streptomyces hydrogenans metabolites can be used as safe biocontrol agents against Meloidogyne incognita and plant growth promoters for Solanum lycopersicum (Sharma et al, 2020 ). Bacillus velezensis is a potential pesticide due to its strong biocontrol activity and ability to strengthen host defense against Magnaporthe oryzae fungi, which cause rice blast disease in plants (Chen et al, 2021 ). An isolate of Trichoderma asperellum increased the resistance in tomato seedling to the disease A. alternata leaf spot (Yu et al, 2021 ).…”
Section: Role Of Biofertilizers In Biotic Stress Managementmentioning
confidence: 99%